2002
DOI: 10.1046/j.1432-1033.2002.02855.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of hydroxylation of saturated fatty acids by recombinant P450foxy produced by an Escherichia coli expression system

Abstract: Cytochrome P450foxy (P450foxy, CYP505) is a fused protein of cytochrome P450 (P450) and its reductase isolated from the fungus Fusarium oxysporum, which catalyzes the subterminal (x-1x-3) hydroxylation of fatty acids. Here, we produced, purified and characterized a fused recombinant protein (rP450foxy) using the Escherichia coli expression system. Purified rP450foxy was catalytically and spectrally indistinguishable from the native protein, but most of the rP450foxy was recovered in the soluble fraction of E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 30 publications
7
45
0
1
Order By: Relevance
“…Substrate inhibition has previously been investigated with CYP505 from Fusarium oxysporum, and inhibition has been reported at concentrations above 0.2 mM of saturated fatty acids, longer than 13 carbons, during in vitro experiments (Kitazume et al 2002). Substrate inhibition of the artificial fusion construct by the substrate dodecanoic acid has been observed in this study, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…Substrate inhibition has previously been investigated with CYP505 from Fusarium oxysporum, and inhibition has been reported at concentrations above 0.2 mM of saturated fatty acids, longer than 13 carbons, during in vitro experiments (Kitazume et al 2002). Substrate inhibition of the artificial fusion construct by the substrate dodecanoic acid has been observed in this study, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…The heme-domain is fused with a diflavin-reductase domain, similar as for BM3, rendering the enzyme self-sufficient. CYP505A1 from Fusarium oxysporum (P450 foxy ) facilitates the hydroxylation of C6:0 to C16:0 fatty acids at the positions ω-1 to ω-3 (for C10:0 and C12:0 position ω-1 is most favored, for C11:0 position ω-2) and suffers in contrast to BM3 from substrate inhibition with fatty acid substrates longer than C13 [121]. Recently, CYP505A30 from the thermostable Myceliophthora thermophila was characterized as fatty acid hydroxylase.…”
Section: Cyp505mentioning
confidence: 99%
“…It has been demonstrated that the K m and k cat values for hydroxylation by other cytochrome P450s can be extremely variable (15,18). P450 bisd exhibited a low k cat value and appeared to be an ineffective enzyme for the hydroxylation of BPA.…”
mentioning
confidence: 99%